Effectors of Root-Knot Nematodes: An Arsenal for Successful Parasitism - Jagdale, Shounak; Rao, Uma; Giri, Ashok P. (Frontiers in Plant Science, 2021)
Root-knot nematodes (RKNs) are notorious plant-parasitic nematodes first recorded in 1855 in cucumber plants. They are microscopic, obligate endoparasites that cause severe losses in agriculture and horticulture. They evade plant immunity, hijack the plant cell cycle, and metabolism to modify healthy cells into giant cells (GCs) – RKN feeding sites. RKNs secrete various effector molecules which suppress the plant defence and tamper with plant cellular and molecular biology. These effectors originate mainly from sub-ventral and dorsal oesophageal glands. Recently, a few non-oesophageal gland secreted effectors have been discovered. Effectors are essential for the entry of RKNs in plants, subsequently formation and maintenance of the GCs during the parasitism. In the past two decades, advanced genomic and post-genomic techniques identified many effectors, out of which only a few are well characterized. In this review, we provide molecular and functional details of RKN effectors secreted during parasitism. We list the known effectors and pinpoint their molecular functions. Moreover, we attempt to provide a comprehensive insight into RKN effectors concerning their implications on overall plant and nematode biology. Since effectors are the primary and prime molecular weapons of RKNs to invade the plant, it is imperative to understand their intriguing and complex functions to design counter-strategies against RKN infection.